Monomer-Induced Customization of UV-Cured Atelocollagen Hydrogel Networks - Liang, He; Russell, Stephen J.; Wood, David J.; Tronci, Giuseppe (Frontiers in Chemistry, 2018)
The covalent functionalisation of type I atelocollagen with either 4 vinylbenzyl or methacrylamide residues is presented as a simple synthetic strategy to achieve customisable, cell-friendly UV cured hydrogel networks with widespread clinical applicability. Molecular parameters, i.e. the type of monomer, degree of atelocollagen functionalisation and UV curing solution, have been systematically varied and their effect on gelation kinetics, swelling behaviour, elastic properties and enzymatic degradability investigated. UV-cured hydrogel networks deriving from atelocollagen precursors functionalised with equivalent molar content of 4 vinylbenzyl (F4VBC= 18±1 mol.%) and methacrylamide (FMA= 19±2 mol.%) adducts proved to display remarkably-different swelling ratio (SR= 1963±58–5202±401 wt.%), storage modulus (G’= 17±3–390±99 Pa) and collagenase resistance (µrel= 18±5–56±5 wt.%), similarly to the case of UV cured hydrogel networks obtained with the same type of methacrylamide adduct, but varied degree of functionalisation (FMA= 19±2–88±1 mol.%). UV-induced network formation of 4VBC functionalised atelocollagen molecules yielded hydrogels with increased stiffness and enzymatic stability, attributed to the molecular rigidity of resulting aromatised crosslinking segment, whilst no toxic response was observed with osteosarcoma G292 cells. Although to a lesser extent, the pH of the UV-curing solution also proved to affect macroscopic hydrogel properties, likely due to the altered organisation of atelocollagen molecules during network formation. By leveraging the knowledge gained with classic synthetic networks, this study highlights how the type of monomer can be conveniently exploited to realise customisable atelocollagen hydrogels with controlled structure-property relationships to meet the requirements of unmet clinical applications.